Neocortical calretinin neurons in primates: increase in proportion and microcircuitry structure - Domagoj eDžaja; Ana eHladnik; Ivana eBičanić; Marija eBaković; Zdravko ePetanjek; Zdravko ePetanjek (Frontiers in Neuroanatomy, 2014)
In this mini review we first point at the expansion of associative cortical areas in primates as well as at the intrinsic changes in the structure of the cortical column. There is a huge increase in proportion of glutamatergic cortical projecting neurons located in the upper cortical layers (II/III). In addition, inside this group a novel class of associative neurons becomes recognized that is important for both, inter-areal and intra-areal columnar integration. By overviewing the literature data we found that there might be also a 50% increase in proportion of neocortical GABAergic neurons between primates and rodents, principally reflecting a 4 to 5 fold increase in proportion of calretinin interneurons. In primates calretinin interneurons might represent 15% of the total neuron number in the upper layers of high order associative areas. Evaluating data about functional properties of their connectivity we hypothesize that an exponential increase in proportion of calretinin interneurons might lead to supra-linear growth in memory capacity of the associative neocortical network. An open question is do we have some new calretinin interneuron subtypes which might substantially change micro-circuitry structure of the primate cerebral cortex.